Educational Loss at Times of Crisis: The Role of Games in Students' Learning in Palestine and Iraq - Ali, Kareema; Burgos, Daniel; Affouneh, Saida (Sustainability, 2023)
This study examines the role of educational games in compensating for educational loss and their impact on students' motivation towards learning during crises in Palestine and Iraq. Additionally, the study considers the challenges facing the employment of this strategy and ways to overcome these challenges. By performing separate open semi-structured interviews with a group of 10 educators from university professors, teachers, and educational supervisors, the study used the qualitative descriptive approach which designs multiple case studies. The results showed the prominent role that educational games play in increasing students' motivation towards learning and compensating for educational loss through what they add to the fun and suspense in the learning process and how they shorten time and effort and help students to engage and cooperate in acquiring knowledge, skills, and values. The results also reveal common challenges that face the employment of educational games. These challenges are social, economic, technological, challenges related to school environment, and psychological challenges. The study shows the possibility of overcoming these challenges by providing funding sources, preparing plans to employ educational games, and developing teachers' capabilities to implement them in their teaching practices.
Keywords: educational games; educational loss; motivation; crises; JCR